Faktor-faktor yang Mempengaruhi Praktik Perataan Laba pada Perusahaan yang Terdaftar di Bursa Efek Jakarta - She Jin, Liauw; Mas'ud Machfoedz, Mas'ud (The Indonesian Journal of Accounting Research, 1998)
Income smoothing practice is a common phenomenon and incurred in several countries. The definition of income smoothing is defined as the way used by the management to reduce the fluctuations of reported income to achieve the target income either artificially (through accounting method) or economically (through transaction). Income smoothing practice is important because this practice can is a result of the disfunctional behaviour which arise as from conflicts among parties who have interest on the financial statements of the companies, especially the income statement.This research is designed to examine factors that can be identified with the incidence of income smoothing practice among listed companies at Jakarta Stock Exchange (JSX). The factors being examined were size, profitability, industrial sectors and operating leverage of the companies. To determine the incidence of income smoothing practice, Eckel index was used. The object of income smoothing in this research is net income. The samples were 53 listed companies at JSX, six years from 1991-1996, with total subsamples of 318 financial statements.Univariate tests (Mann-Whitney, Chi-Square and T-Test) and multivariate tests (logistic regression) were used to identify the factors affecting the income smoothing practice. One-Sample Kolmogorov-Smirnov test was also performed to test the normality of the data being used.The results of Eckel index calculation showed that income smoothing is also practiced by listed companies at JSX. The Descriptive statistics showed that companies in financial institutions sector practiced income smoothing more than those in manufacturing sectors. The test results of univariate tests showed that industrial sectors and operating leverage are the variables having a significance influence on income smoothing practice. Multivariate tests showed that only operating leverage influences income smoothing practice. In conclusion, from four independent variables being examined, only operating leverage affects the incidence of income smoothing practice.